A new species of Allobates (Anura, Dendrobatidae) from the western flank of the Serranía de Perijá, Colombia - Anganoy-Criollo, Marvin (Zootaxa, 2012)
A new species of nurse frog is described from the Serranía de Perijá, Colombia. The new species is the fourth trans-Andean species in the genus Allobates. The new species is very similar to Allobates wayuu and also resembles A.melanolaemus, A. mcdiarmidi, A. niputidea, A. spumaponens and A. trilineatus, but differs in the type of posterior joiningof the dorsolateral stripe, pattern of coloration on the gular-chest region in males, ventral coloration in females, and by thepattern of the oblique lateral stripe; moreover, their similar are geographically isolate. Although Allobates is the secondlargest genus of dendrobatids (45 species), in Colombia, it has a diversity of thirteen species (including the new one described herein), nine cis-Andean and four trans-Andean. It is probable that the diversity in Colombia is underestimated.